1978
DOI: 10.1088/0022-3727/11/17/005
|View full text |Cite
|
Sign up to set email alerts
|

Gain, fluorescence and energy extraction characteristics of photostabilised atmospheric pressure UV nitrogen lasers

Abstract: The authors report on a detailed investigation of the gain, fluorescence and energy extraction characteristics of photopreionisation-stabilised atmospheric pressure UV nitrogen lasers excited at pump powers of up to approximately 5*109 W cm-3. The lasers provide specific power outputs of approximately 6 MW cm-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The interest arises due to the fact that N 2 -laser can be easily made, and is a useful optical device in any optical research laboratory. From the theoretical point of view, although many papers have been published on the subject [1][2][3][4][5][6][7][8][9][10], there are many questions that have not been properly answered up to the present years. For example, when the rate equations are used to calculate the output characteristics of the laser, there is an ambiguity for selecting appropriate electron impact-excitation cross-sections from the ground to the upper, C 3 P u , and lower B 3 P g electronic energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…The interest arises due to the fact that N 2 -laser can be easily made, and is a useful optical device in any optical research laboratory. From the theoretical point of view, although many papers have been published on the subject [1][2][3][4][5][6][7][8][9][10], there are many questions that have not been properly answered up to the present years. For example, when the rate equations are used to calculate the output characteristics of the laser, there is an ambiguity for selecting appropriate electron impact-excitation cross-sections from the ground to the upper, C 3 P u , and lower B 3 P g electronic energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the laser pulse energy in both cases revealed that pre-ionisation by UV-light from the spark gap does not play any notice able role, as was already mentioned in [1]. On the other hand, pre-ionization by corona discharge over the capacitor foil between the laser electrodes cannot be excluded; Bergmann and Hasson have positively used this effect already in 1978 [6].…”
Section: Resultsmentioning
confidence: 81%
“…8 Furthermore, we have shown that gain coefficient depends strongly on the length of laser tube, or laser channel, in both longitudinally excited 8 ͑LE͒ and transversely excited ͑TE͒ N 2 lasers. 3 Papakin and Sonin, on the other hand, have further studied the behavior of the gain coefficient for determination of high gain values, the nature of broadening, and the width of line emission, using a single oscillator laser system. We further realized experimentally that in this laser, the saturation energy density is linearly related to the output energy density, and the effect of the corona preionization and He buffer gas on the laser parameters were also investigated.…”
Section: Introductionmentioning
confidence: 99%